2005
DOI: 10.1103/physrevd.71.075014
|View full text |Cite
|
Sign up to set email alerts
|

Pair production of charged Higgs bosons from bottom-quark fusion

Abstract: For very large values of tan, the charged Higgs boson pair production via b b annihilation can proceed dominantly at the large hadron collider (LHC). We calculated the cross sections of the charged Higgs boson pair production via subprocess b b ! H H ÿ at the LHC including the next-to-leading order (NLO) QCD corrections in the minimal supersymmetric standard model (MSSM). We find that the NLO QCD corrections can significantly reduce the dependence of the cross sections on the renormalization and factorization … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…For the production of a pair of Higgs bosons, the NLO correction was first obtained in [51]. Later on, NLO corrections have been obtained for this channel considering several BSM scenarios [52][53][54]. For the latter, the bottom quark annihilation process dominates over the gluon fusion even at LO level.…”
Section: Jhep05(2019)030mentioning
confidence: 99%
“…For the production of a pair of Higgs bosons, the NLO correction was first obtained in [51]. Later on, NLO corrections have been obtained for this channel considering several BSM scenarios [52][53][54]. For the latter, the bottom quark annihilation process dominates over the gluon fusion even at LO level.…”
Section: Jhep05(2019)030mentioning
confidence: 99%
“…This was related to the key issue of defining the right factorisation scale µ F as log(µ F /m b ) terms that are resummed in the b-parton picture could overestimate the cross section if µ F were too big. The calculation of the NLO QCD corrections [35,44] solved the issue and confirmed that the…”
Section: Drell-yan and B B Productionmentioning
confidence: 67%
“…The cross section is dependent on tan β . In the MSSM the SUSY-QCD corrections are dominated by negative resummed ∆ b -terms in the bottom quark Yukawa coupling and depend strongly on the MSSM spectrum [35,44].…”
Section: Drell-yan and Bb Productionmentioning
confidence: 99%
“…Note added: While we were in the process of finalizing this work, another paper [40] appeared in which the authors present results which correspond to parts of our sections II and V.…”
Section: Discussionmentioning
confidence: 82%